2005
DOI: 10.1111/j.1600-6143.2004.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Neogenesis in Murine Cardiac Allografts Undergoing Chronic Rejection

Abstract: Lymphoid neogenesis is the process by which ectopic lymphoid accumulations that resemble lymph nodes arise in nonlymphoid tissues. Such lymphoid accumulations, known as tertiary lymphoid organs (TLO), are observed in chronic autoimmunity and they propagate immune pathology by setting up local antigen presenting sites. Whether lymphoid neogenesis occurs in transplanted organs and contributes to rejection is not well understood. To begin to address this question, we retrospectively analyzed 319 murine cardiac al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 20 publications
4
85
3
Order By: Relevance
“…Although a specific increase in infiltrating APC in chronic AMR has not been formally reported to date, this is likely given that an increased monocyte infiltrate has been reported in C4d ϩ cases of acute rejection, 26 and a recent report showed that C4d ϩ biopsies have a higher monocyte/T cell ratio than C4d Ϫ ones. 27 Although an increase in B cell infiltration has been reported in chronic AMR, resulting from a phenomenon known as lymphoid neogenesis, 28 it is unlikely that TRIB1 is increased as a result of this because TRIB3, which is expressed primarily by B cells, was not increased and activated B cells downregulate their TRIB1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific increase in infiltrating APC in chronic AMR has not been formally reported to date, this is likely given that an increased monocyte infiltrate has been reported in C4d ϩ cases of acute rejection, 26 and a recent report showed that C4d ϩ biopsies have a higher monocyte/T cell ratio than C4d Ϫ ones. 27 Although an increase in B cell infiltration has been reported in chronic AMR, resulting from a phenomenon known as lymphoid neogenesis, 28 it is unlikely that TRIB1 is increased as a result of this because TRIB3, which is expressed primarily by B cells, was not increased and activated B cells downregulate their TRIB1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our group (18,21,23) and others (17,41) have contributed to document the role of lymphoid neogenesis, namely, the progressive organization of inflammatory cells into structures that morphologically resemble secondary lymphoid organs (42) during chronic rejection. Accumulating evidence indeed suggests that intragraft ectopic germinal centers support the maturation of a local humoral immune response, which in turn contributes to tissue destruction (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, formation of tertiary lymphoid organs and an association between alloimmunity and lymphoid neogenesis in the target organ were recently demonstrated in a murine model of chronic cardiac allograft rejection. 39 Inflammation-associated nonencapsulated lymphoid structures in nonlymphoid organs are assumed to be a key determinant in the pathogenesis of autoimmune and alloimmune diseases. They are characterized by antigen-driven immune responses which first lead to a nonorganized infiltrate predominantly composed of T cells and sporadic B cells.…”
Section: Discussionmentioning
confidence: 99%